Studi Analisis Cyberbullying terhadap Liam James Payne dalam Perspektif Hukum Hak Asasi Manusia - Muthia Ivana Zahra; Majda El Muhtaj (Pusat Riset dan Inovasi Nasional, 2026)
The phenomenon of cyberbullying has emerged as a negative consequence of the global expansion of social media usage, which can affect all groups, including celebrities who often become the center of media attention. The widespread use of social media makes it easier for individuals to leave comments or opinions without clear boundaries, often violating social norms and values. This is closely related to the principle of Human Rights, particularly Article 19 of the Universal Declaration of Human Rights (UDHR), which addresses the freedom of expression. This study uses the library research method, analyzing the phenomenon of cyberbullying experienced by celebrity Liam Payne from a Human Rights perspective. Data is analyzed through data reduction, data display, and data verification, sourced from e-books and e-journals. The main objective of this research is to provide a deeper understanding of the phenomenon of cyberbullying and link it to the freedom of expression rights outlined in human rights law. This research also aims to educate readers on the importance of creating a safer and healthier social media environment, free from the fear of experiencing online bullying (cyberbullying). By understanding the Human Rights concept related to freedom of expression, it is hoped that society will engage more responsibly on social media and reduce instances of cyberbullying among celebrities and the general public.